Pattern of Medical Disorders in Adults in District Lakki Marwat, Pakistan - Muhammad Usman; Shazia Tabassum; Ikram-ullah Khan (Gomal Journal of Medical Sciences, 2004)
Background: The objective of this study was to determine the pattern of various diseases /problems with which the patients present to a medical specialist in District Lakki Marwat.